Análisis del marco tarifario del servicio público de acueducto y alcantarillado: una aproximación desde un análisis global y local (2021)
A global and local analysis regarding the rates of the aqueduct and sewerage system in Colombia. Analysis of the parameters that govern said tariff framework and its behavior in the different Colombian socio-economic strata.